The Role of the International Court of Justice in Resolving Disputes Between Countries - Abi Dzar Al-Ghifari; Muhammad Rafi Indra Azmi (AT-TAFAHUM: Journal of Law, 2020)
The International Court of Justice (ICJ) is the principal organ of the United Nations, authorized to peacefully resolve disputes between states. This study aims to analyze in depth the role, function, and effectiveness of the International Court of Justice in resolving international disputes. The research method used is normative legal research with a conceptual approach, legislation, and case studies. The results show that the International Court of Justice has made a significant contribution to maintaining global stability through legal dispute resolution, although it still faces various challenges such as limited jurisdiction and low levels of state compliance with its decisions. Going forward, the International Court of Justice has the opportunity to expand its role in global issues such as environmental disputes, human rights, and maritime conflicts.